Refounding of the activity concept? Towards a federative paradigm for modeling and simulation. (February 2013) - Muzy, Alexandre; Varenne, Franck; Zeigler, Bernard P; Caux, Jonathan; Coquillard, Patrick; Touraille, Luc; Prunetti, Dominique; Caillou, Philippe; Michel, Olivier; Hill, David RC
Currently, the widely used notion of activity is increasingly present in computer science. However, because this notion is used in specific contexts, it becomes vague. Here, the notion of activity is scrutinized in various contexts and, accordingly, put in perspective. It is discussed through four scientific disciplines: computer science, biology, economics, and epistemology. The definition of activity usually used in simulation is extended to new qualitative and quantitative definitions. In computer science, biology and economics disciplines, the new simulation activity definition is first applied critically. Then, activity is discussed generally. In epistemology, activity is discussed, in a prospective way, as a possible framework in models of human beliefs and knowledge.